Mejoramiento de procesos en el área administrativa de la Empresa Electrificaciones Ecuador S.A. (ELECDOR) dedicada a la elaboración de postes de hormigón armado, subtrasmisión, trasmisión y telecomunicaciones, ubicada en el sector norte de la ciudad de Quito. - Andrade Salazar, Wilson Oswaldo (2013)
This thesis project aims to develop a process improvement in the administrative area of the company Electrificaciones Ecuador SA This is a subsidiary company in Ecuador ELECTRIFICACIONES DEL NORTE SA (ELECNOR) domiciled in Spain, at Ecuador is among the group of top 10 enterprises in construction of substations and electrical lying structures. Chapter one details the approach to the problem, with their respective justification and objectives proposed to solve the research problem, besides the theoretical framework helps to have more knowledge of what was applied in the corresponding chapters.